IMPLEMENTASI HADIS NIAT DALAM PEMBENTUKAN MOTIVASI BELAJAR SANTRI DI PONDOK PESANTREN MAHASANTRI BAITUL ILMI JEMBER - Fikriyah Hanim; Abdullah; Matkur (At Turots: Jurnal Pendidikan Islam, 2026)
Sincere intention for Allah is the main foundation in studying in Islamic boarding schools, distinguishing the blessings and benefits of knowledge obtained by students, and determining the value of each deed as emphasized in the hadith of the Prophet Muhammad SAW: "Indeed, every deed depends on its intention." This study aims to examine the relationship between the intention and motivation of students to learn in Islamic boarding school-based education, by emphasizing the values of sincerity, intrinsic motivation, and the role of the religious community. The study used a qualitative case study approach at the Baitul Ilmi Islamic boarding school in Jember, with triangulation techniques for data validity. The results of the study indicate that fostering the right intention forms a strong and sustainable learning motivation. Students who study for Allah, driven by sincerity, responsibility, and spiritual awareness, have high intrinsic motivation so that they are more consistent, disciplined, and obtain achievements and a complete meaning of learning both academically and spiritually. In addition, the Islamic boarding school community through the role of kyai, ustadz, and the religious environment strengthens the formation of intention and motivation to learn collectively. In contrast, the intention to learn based on worldly motives tends to produce weak and easily faded motivation. Thus, sincere intention is the primary driving force behind students' motivation to learn in Islamic boarding schools, in line with Islamic educational values that not only pursue academic success but also foster character and closeness to God Almighty.